1968
DOI: 10.1182/blood.v32.5.811.811
|View full text |Cite
|
Sign up to set email alerts
|

Brief Report: Plasma Concentrations of Hemopexin, Haptoglobin and Heme in Patients with Various Hemolytic Diseases

Abstract: Plasma concentrations of hemopexin, haptoglobin and heme were determined in patients with various hemolytic diseases. Diminished concentrations of hemopexin were found only when the concentrations of haptoglobin were decreased; the former were not in all instances lowered to the same extent as the haptoglobin levels. Invariably, high concentrations of heme were associated with low concentrations of hemopexin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
157
1
5

Year Published

1975
1975
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 302 publications
(188 citation statements)
references
References 8 publications
8
157
1
5
Order By: Relevance
“…Before TPE, all our patients had highly elevated heme levels compared to stable SCD patients (mean 6 SD, 4.2 6 1.1 mmol/L; range, 0-20 mmol/L) 3 and very low Hp levels, although only Patient 1 also had very low Hx concentrations ( Table 2). This is consistent with previous observation that Hx is never diminished without reduction in Hp 42 and in vitro studies that with oxyHb excess, Hx activity is spared until Hp becomes saturated. 71 Also, some Hx may be recycled after receptor uptake in contrast to Hp being degraded.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Before TPE, all our patients had highly elevated heme levels compared to stable SCD patients (mean 6 SD, 4.2 6 1.1 mmol/L; range, 0-20 mmol/L) 3 and very low Hp levels, although only Patient 1 also had very low Hx concentrations ( Table 2). This is consistent with previous observation that Hx is never diminished without reduction in Hp 42 and in vitro studies that with oxyHb excess, Hx activity is spared until Hp becomes saturated. 71 Also, some Hx may be recycled after receptor uptake in contrast to Hp being degraded.…”
Section: Discussionsupporting
confidence: 94%
“…[4][5][6][7][8]15,[36][37][38] The chronic hemolysis of SCD continuously releases Hb into the plasma, 39,40 resulting in steady-state depletion of Hp in 50% to 90% and of Hx in 10% to 30% of patients. 3,41,42 Brazilian children with steady-state SS disease (n 5 173) had mean plasma Hp and Hx levels of 8 and 14% of healthy AA control children, respectively, and SC children (n 5 93) likewise had levels of 16 and 39%, respectively. 43 Contributing to depletion, Hp and Hx may be catabolized upon endocytosis without sufficient compensatory increases in biosynthesis.…”
Section: Results: Plasma Concentrations Of Hp and Hxmentioning
confidence: 99%
“…Cell-free haemoglobin is rapidly converted to methaemoglobin with liberation of the haem group, which may also elicit cytotoxic and inflammatory-mediated kidney damage (Tracz et al, 2007;Nath & Katusic, 2012). In chronic haemolytic disease states including SCA, the scavengers of free haemoglobin (haptoglobin) and free haem (haemopexin) are consumed resulting in increased circulation of cell-free haemoglobin and haem (Muller-Eberhard et al, 1968).…”
Section: Discussionmentioning
confidence: 99%
“…Muller-Eberhard & Bashore (1970) found that in cases of Rh isoimmunization the ratio of haemopexin to albumin in amniotic fluid fell during severe fetal haemolysis. The concentration of haemopexin in adult and neonatal serum falls when haemolysis occurs for any reason (Muller-Eberhard et al, 1968;Sears, 1969). This is believed to occur as a result of the haemopexin-haem complexes being removed from the serum by the liver (Muller-Eberhard, Liem, Hanstein & Saarinen, 1969).…”
Section: (Ii) Simple Quantitative Studiesmentioning
confidence: 99%